Solution of integral equations for multivalued maps in fuzzy b -metric spaces using Geraghty type contractions - Rashid Ali; Faisar Mehmood; Aqib Saghir; Hassen Aydi; Saber Mansour; Wajdi Kallel (AIMS Mathematics, 2023)
In this article, the notion of Hausdorff fuzzy $ b $-metric space is studied. Some fixed point results for multivalued mappings using Geraghty type contractions in $ G $-complete fuzzy $ b $-metric spaces are established. To strengthen the results, an illustrative example is furnished. A fuzzy integral inclusion is constructed as an application of fixed point result which shows the validity of the proved results. The presented outcomes are the generalization of the existing results in literature.